Optimal sizing methodology for photovoltaic and wind hybrid rooftop generation systems in residential low voltage distribution networks. (October 2018) - Behravesh, Vahid; Akbari Foroud, Asghar; Keypour, Reza
Highlights: Studying the effects of high penetration levels of residential PV-WT hybrid systems. Determining the optimal size of PV and WT parts. Investigating the impacts of control algorithms used in the inverters DERs. Increase accuracy of the study results by using the data with a 5-min resolution. Abstract: Solar and wind energies are interminable, freely accessible and environmentally-friendly energy resources. Nevertheless, if employed independently, due to their unstable nature, they are not completely reliable. The amalgamation of these two types of energy resources will result in reduced fluctuations of each of them and increase the overall energy production. In the recent years, with the increased electrical demands of residential homes and electrical vehicles (EVs), and due to the rapid advancements in power electronics, application of photovoltaic (PV) and wind turbine (WT) hybrid rooftop generation systems (PV-WT hybrid systems) has been considered as the best choice to supply the consuming loads of residential homes. This paper proposes a novel methodology to optimize the size of PV-WT hybrid systems in residential low voltage distribution networks (residential networks). In the presented methodology, the optimal combination of PV-WT hybrid systems for an unbalanced three-phase four-wire low voltage residential network in a future scenario is obtained with a concentration of single-phase distributed energy resources (DERs). This methodology considers the measured meteorological and consuming load data within a year with a 5-min resolution. Also, the following factors are evaluated in the DIgSILENT PowerFactory15.1.7 software environment: voltage profile, voltage imbalance, transformer loading, and curtail dump power of PV-WT hybrid systems. The objective of this study is to investigate the effects of different size combinations of PV and WT systems on voltage behavior of a residential network, low voltage (LV) transformer loading, and curtail dump power of PV-WT hybrid systems during a year. Consequently, an optimal and suitable combination of PV and WT capacities is obtained in a PV-WT hybrid system.